PSXIV-35 Low feed intake induced gut microbiome alteration leads to exacerbated bile acid metabolism in piglets during transition periods. (7th December 2018) - Lin, S; Yang, X; Yang, J; Fang, Z; Zhong, H; Li, J; Che, L; Feng, B; Lin, Y; Xu, S; Wu, D; Fang, Z
Abstract: The present study was conducted to determine the alteration of bile acid profile and signaling in piglets during transition periods and the potential association with gut microbiome. A total of 24 piglets were included in this study. Twelve suckling piglets euthanized at 21 or 28 days of age were designated as D21 or D28 group respectively. Twelve piglets weaned at 21 days of age and fed solid feed until 28 days of age were designated as low feed intake (LFI, ingested nutrients could hardly meet maintenance requirements) group or normal feed intake (NFI, ingested nutrients higher than maintenance requirements) group, respectively. Jugular concentrations of conjugated deoxycholic acid (DCA) and lithocholic acid (LCA) were higher (P<0.05) in LFI pigs than pigs in other groups. Increased (P<0.05) levels of LCA, conjugated LCA and conjugated DCA in portal blood as well as conjugated and unconjugated DCA in colon contents were observed in LFI pigs when compared with NFI pigs. Compared with NFI pigs, LFI pigs had higher (P<0.05) mRNA expression of Fibroblast growth factor 19 and small heterodimer partner (SHP) in ileum and higher (P<0.05) mRNA expression of SHP while lower (P<0.05) mRNA expression of Cholesterol 7 alpha-hydroxylase in liver. The 16srRNA sequence data indicated a more diverse microbiome community in LFI pigs. Compared with NFI pigs, LFI pigs had higher (P<0.05) relative abundance of Clostridium_scindens, an important bacterial species with 7a-dehydroxylating activity which is crucial in the conversion of primary bile acids to secondary bile acids. Taken together, our results indicated that exacerbated bile acid metabolism was induced by low feed intake with the level of toxic bile acids DCA and LCA increasing significantly. Low feed intake induced microbiome shift seemed to be responsible for the alteration of bile acid profile and subsequent FXR signaling.